All polymer bulk heterojunction organic electrochemical transistors with balanced ionic and electronic transport - Wu, Xihu (2022)
Rapid development of organic electrochemical transistor (OECTs)-based circuits bring new opportunities for next-generation integrated bioelectronics. All polymer bulk heterojunction (BHJ) offers an attractive, inexpensive alternative to achieve efficient ambipolar OECTs, and building blocks of logic circuits constructed from them, but have not been investigated till date. Here, we report the first all polymer BHJ-based OECTs, consisting of a blend of new p-type ladder conjugated polymer and the state-of-the-art n-type ladder polymer. The optimized BHJ OECTs exhibit balanced ambipolar transistor performance, having uC* values of 2.72±1.04 and 1.36±0.81 F cm-1 V-1 s-1 as p-type and n-type channels, respectively. The whole ladder-type polymer BHJ also proved that side chains are not necessary for good ion transport. Instead, the polymer nanostructures play a critical role in the ion penetration and transport and thus the device performance. It also provides a facile strategy and simplifies the fabrication process, forgoing the need to pattern multiple active layers. In addition, the development of complementary metal–oxide–semiconductor (CMOS)-like OECTs allows us to pursue advanced functional logic circuitry, including inverter and NAND gate as well as for amplifying electrophysiology signals. Our work opens a new approach in the design of new materials for OECTs and will contribute to the development of organic heterojunctions for ambipolar OECTs towards high performing logic circuits.